Applied Hydrogeology of Fractured Rocks Second Edition - Singhal, B.B.S.; Gupta, R.P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Hydrogeology is a topical and growing subject as the earth's water resources become scarcer and more vulnerable. More than half of the surface area of continents is covered with hard rocks of low permiability. This book deals comprehensively with the fundamental principles for understanding the hydrogeological characteristics of rocks, as well as exploration techniques and assessment. It also provides in depth discussion on structural mapping, remote sensing, geophysical exploration, GIS, groundwater flow modelling and contaminant transport, field hydraulic testing including tracer tests, groundwater quality, geothermal reservoirs, managed aquifer recharge, and resources assessment and management. Hydrogeological aspects of various lithology groups, including crystalline rocks, volcanic rocks, carbonate rocks and clastic formations have been dealt with separately, using and discussing examples from all over the world. It will be an invaluable text book cum reference source for postgraduate students, researchers, exploration scientists and engineers engaged in the field of groundwater development in fractured rocks. Applied Hydrogeology of Fractured Rocks - Second Edition is thoroughly revised and extended with a new chapter, updated sections, many new examples, and expanded and updated references. Audience: This book will be an invaluable text book cum reference source for postgraduate students, researchers, exploration scientists and engineers engaged in the field of groundwater development in fractured rocks. From the reviews of the previous edition: "In all, Applied Hydrogeology of Fractured Rocks helps fill the need for a primer in fractured rocks hydrology. It should prove particularly useful to consultants confronted with fractured rock systems, and are in need of some pointers." (M. Becker, Hydrogeology Journal (2002) 10: 600)
and Basic Concepts -- Fractures and Discontinuities -- Hydrogeological Investigations -- Remote Sensing -- Geophysical Exploration -- Geographical Information System (GIS) -- Principles of Groundwater Flow and Solute Transport -- Hydraulic Properties of Rocks -- Estimation of Hydraulic Properties of Aquifers -- Tracer and Isotope Techniques -- Groundwater Quality -- Groundwater Contamination -- Hydrogeology of Crystalline Rocks -- Hydrogeology of Volcanic Rocks -- Hydrogeology of Carbonate Rocks -- Hydrogeology of Clastic Formations -- Water-wells -- Geothermal Reservoirs and Hot Dry Rock Systems -- Groundwater Modeling -- Assessment and Management of Groundwater Resources.
Keywords: Geography; Hydraulic engineering; Remote sensing; Earth Sciences; Hydrogeology; Geotechnical Engineering & Applied Earth Sciences; Remote Sensing/Photogrammetry.